âINDEPENDENT ENERGY COMPANYâ SOLUSI INDUK PEMANFAATAN ALIRAN AIR PADA INDUSTRI SEBAGAI SUPPLYER MANDIRI ENERGI LISTRIK UNTUK PERUSAHAAN BERBASIS RAMAH LINGKUNGAN 2037 - Dahliyah, Nailil; Hermanto, Anton; Wahyundari, Evita (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
The prediction of future energy needs mention that people are bigger and energy sources in use currently predicted will fail. And it will really happen in about year 2300. Based on those problems, and we take an idea to make renewable energy source that we call independent energy company. We know that every building available almost had drainages on pipe. The Principle on mikrohidro we use to make an instrument that utilizes the flow of water to convert the kinetic energy into electrical energy. This system apply the principle of fluid mechanics. Water flowing on water pipes have potential and kinetic energy that can be utilized to rotate turbine which connected with the generator axis that would change this mechanical energy into electrical energy. Furthermore, electrical energy can directly used or stored first in a battery and used anytime. With the success of this system work, the industry is expected to meet its own electricity needs to be able to reduce the amount of electrical energy consumption sourced from fossil fuels or petroleum.